Burkholderia pseudomallei Evades Nramp1 (Slc11a1)- and NADPH Oxidase-Mediated Killing in Macrophages and Exhibits Nramp1-Dependent Virulence Gene Expression - Muangsombut, Veerachat; Withatanung, Patoo; Srinon, Varintip; Chantratita, Narisara; Stevens, Mark P.; Blackwell, Jenefer M.; Korbsrisate, Sunee (Frontiers in Cellular and Infection Microbiology, 2017)
Bacterial survival in macrophages can be affected by the natural resistance-associated macrophage protein 1 (Nramp1; also known as solute carrier family 11 member a1 or Slc11a1) which localizes to phagosome membranes and transports divalent cations, including iron. Little is known about the role of Nramp1 in Burkholderia infection, in particular whether this differs for pathogenic species like B. pseudomallei causing melioidosis or non-pathogenic species like B. thailandensis. Here we show that transfected macrophages stably expressing wild-type Nramp1 (Nramp1+) control the net replication of B. thailandensis, but not B. pseudomallei. Control of B. thailandensis was associated with increased cytokine responses, and could be abrogated by blocking NADPH oxidase-mediated production of reactive oxygen species but not by blocking generation of reactive nitrogen species. The inability of Nramp1+ macrophages to control B. pseudomallei was associated with rapid escape of bacteria from phagosomes, as indicated by decreased co-localization with LAMP1 compared to B. thailandensis. A B. pseudomallei bipB mutant impaired in escape from phagosomes was controlled to a greater extent than the parent strain in Nramp1+ macrophages, but was also attenuated in Nramp1− cells. Consistent with reduced escape from phagosomes, B. thailandensis formed fewer multinucleated giant cells in Nramp1+ macrophages at later time points compared to B. pseudomallei. B. pseudomallei exhibited elevated transcription of virulence-associated genes of Type VI Secretion System cluster 1 (T6SS-1), the Bsa Type III Secretion System (T3SS-3) and the bimA gene required for actin-based motility in Nramp1+ macrophages. Nramp1+ macrophages were found to contain decreased iron levels that may impact on expression of such genes. Our data show that B. pseudomallei is able to evade Nramp1- and NAPDH oxidase-mediated killing in macrophages and that expression of virulence-associated genes by pathogenic B pseudomallei is enhanced in macrophages expressing wild-type compared to non-functional Nramp1. B. thailandensis has been proposed as surrogate for B. pseudomallei in the study of melioidosis however our study highlights important differences in the interaction of these bacteria with macrophages. □